2019
DOI: 10.22158/ibes.v1n2p95
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Export and Economic Growth in Tanzania

Abstract: This study explored the causal relationship between exports and economic growth in Tanzania. It analyzed time series data for the period of 1980 to 2015. Economic growth is measured in terms of growth per cent while exports are measured in percentage change of goods and services sold abroad. Econometrics analysis was employed in the due course. Such procedures as testing for the presence of unit root, co-integration and causality were done. Furthermore, the Johansen co-integration and Granger causality tests w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…These insights have shown that economic growth promotes expansion of exports in Luxembourg and Iceland. These results are in line with other previous investigations by Mishra (2011), Tekin (2012, Abbas (2012), andDimonso andUtonga (2019). This means that a growing economy spurs exporting of goods and services more than exports manage to stimulate economic growth.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These insights have shown that economic growth promotes expansion of exports in Luxembourg and Iceland. These results are in line with other previous investigations by Mishra (2011), Tekin (2012, Abbas (2012), andDimonso andUtonga (2019). This means that a growing economy spurs exporting of goods and services more than exports manage to stimulate economic growth.…”
Section: Discussionsupporting
confidence: 93%
“…The results have suggested that the focus should be on increasing production which, in the long-run, has an impact upon both trade and economic performance. Dimonso and Utonga (2019) have revealed that in the long-run, economic activities impact on exports in Tanzania. Hussaini et al (2015) studied an export-growth nexus in India between 1980 and 2013.…”
Section: Findings Of Recent Investigationsmentioning
confidence: 99%
“…In Tanzania Dimoso and Utonga [34] explored the causal relationship between exports and economic growth by analyzing annual time series data from 1980 to 2015. The causality test results showed the existence of causality which runs from economic growth to exports.…”
Section: Literature Reviewmentioning
confidence: 99%